Physical and Numerical Modeling of Flow in a Meandering Channel - Yilmazer, Cem; Guener, H. Anil Ari (MDPI, 2024)
In this study, flow behavior in a meandering channel was investigated experimentally and numerically. The experiments were carried out for nine different cases on a channel consisting of 180 degrees and 120 degrees angle bends following successively. Measurements were conducted employing Acoustic Doppler Velocimetry (ADV) at 13 different points in the inner, middle, and outer bends of the sections located at significant bends along the channel. Depth-averaged velocity, velocity profiles, bed shear stress, and turbulence kinetic energy parameters were considered to understand the flow behavior in the meandering channel. A 1:1 scale numerical model of the experimental setup was generated using the Computational Fluid Dynamics (CFD) method through the verified FLOW-3D software (HYDRO 2022R1). It was found to be successful in estimating all parameters and was capable of investigating the flow behavior in the meandering channel. Additionally, a mesh independence study was performed, and four different turbulence models were compared. As a result, as the flow encountered the first meander in the channel, secondary flow occurred, and lateral momentum transfer took place. Therefore, velocity increased by approximately 30% from the first meander of 180 degrees angles to the second meander of 120 degrees angles. Therefore, the most critical zone was the inner bend of the 120-angle meander.
Keywords: meandering channel; flow measurement; computational fluid dynamics; FLOW-3D; validation; velocity profile; bed shear stress; turbulence kinetic energy; acoustic doppler velocimetry; SECONDARY FLOW; TURBULENCE; Environmental Sciences & Ecology; Water Resources